Kajian Literatur Sistematis Performansi Sistem Komunikasi Berbasis Software Defined Radio: Indonesia - Muhamad Ilham; Andi Ahmad Dahlan; Yulindon Yulindon (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The rapid development of wireless communication requires flexible and efficient systems in spectrum utilization. Software Defined Radio (SDR) enables communication functions to be implemented through software, increasing system flexibility. This study aims to analyze the performance of SDR-based digital communication systems using a Systematic Literature Review (SLR). A total of 18 articles published between 2021–2026 were analyzed based on key performance parameters. The results show that accuracy or detection probability is the most dominant parameter (22%), followed by throughput, latency, and system efficiency (17%), while Bit Error Rate (BER) accounts for 11%. The study also identifies trade-offs among performance parameters in SDR systems. These findings provide insights for optimizing future SDR-based communication systems.